Vloga naravnogeografskih značilnosti porečja pri sonaravnem upravljanju z vodnimi viri v porečju Kamniške Bistrice - Brečko Grubar, Valentina (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
The paper discusses natural-geographical characteristics of the Kamniška Bistrica drainage basin and their influence of water resources. Different water resources occur in the Kamniška Bistrica drainage basin, which all together represent a large amount of water. Great differences exist within the Kamniška Bistrica drainage basin between the naturalgeographical characteristics of its sections, which are discussed in the paper in relation to the characteristics of water resources.
Keywords: porečja; površinske vode; vodotoki; vodni viri; oskrba z vodo; podtalnica; hidrogeografija; Kamnik Bistrica; Kamniška Bistrica